Mental health and COVID-19 perceptions in a predominant black population in the Eastern Caribbean: an exploratory study of residents of Barbados. Issue 2 (18th November 2021) - King, Jolene; Devonish, Dwayne
Abstract : Purpose: The purpose of this study is to examine the mental health challenges of residents of Barbados during the COVID-19 pandemic and the relationships between residents' demographics, COVID-19 perceptions and mental health outcomes. Design/methodology/approach: The study surveyed 450 predominantly Black Caribbean respondents to examine their mental ill-health on the various dimensions of the General Health Questionnaire (GHQ)-28 measure and the relationships with demographics and COVID-19 perceptions. Findings: Confirmatory factor analysis confirmed the four-factor model solution of GHQ-28 over the single factor solution. Barbadians were generally mild in their mental ill-health on the somatic symptoms, social dysfunction and severe depression dimensions but were at least moderately strained on the anxiety and insomnia dimensions. Younger and unemployed Barbadian respondents reported more adverse mental health outcomes, and perceived severity of COVID-19 infection significantly predicted three of the four dimensions of mental distress (excluding severe depression). Research limitations/implications: The study used a cross-sectional self-report survey research design which does not permit causal inferences. Further research is advised to ascertain the longitudinal effects of COVID-19 perceptions over time on mental health outcomes. Practical implications: The study's findings suggest the need for nation-wide, multi-stakeholder interventions or approaches in responding mental health challenges of the population during this crisis. Originality/value: The study was the first to examine the mental health outcomes, using GHQ-28, in a small Caribbean country – which represents an underserved space in mental health research. It is the first to empirically examine the relationship between COVID-19 perceptions of Afro-Caribbean people in this region and their resultant mental health outcomes.